2020
DOI: 10.3389/fgene.2020.00897
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compound Heterozygous Mutations in CRTAP Cause Rare Autosomal Recessive Osteogenesis Imperfecta

Abstract: Whole-exome sequencing (WES) has advantages over the traditional molecular test by screening 20,000 genes simultaneously and has become an invaluable tool for genetic diagnosis in clinical practice. Here, we reported a family with a child and a fetus presenting undiagnosed skeletal dysplasia phenotypes, while the parents were asymptomatic. WES was applied to the parents and affected fetus to identify the genetic cause of the phenotypes. We identified novel compound heterozygous mutations consisting of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(73 reference statements)
0
6
0
1
Order By: Relevance
“…No mutation was identified in the cfDNA or in gDNAs from fetal umbilical cord tissue. To investigate the underlying genetic defect of the proband, we performed whole-exome sequencing and found novel compound heterozygous mutations in CRTAP gene consisting of SNV and deletion, suggesting the case was a rare autosomal recessive form of OI [52]. The findings supported the true negative result of cfDNA using the established targeted-seq assay.…”
Section: The Sensitivity and Specificity Of Established Targeted-seq ...mentioning
confidence: 55%
See 1 more Smart Citation
“…No mutation was identified in the cfDNA or in gDNAs from fetal umbilical cord tissue. To investigate the underlying genetic defect of the proband, we performed whole-exome sequencing and found novel compound heterozygous mutations in CRTAP gene consisting of SNV and deletion, suggesting the case was a rare autosomal recessive form of OI [52]. The findings supported the true negative result of cfDNA using the established targeted-seq assay.…”
Section: The Sensitivity and Specificity Of Established Targeted-seq ...mentioning
confidence: 55%
“…It is of notice that the mutations result in rare autosomal recessive form of severe OI-related symptoms in family 2 [52] were not detected in the established panel. It is still challenging to detect mutations for autosomal recessive diseases in NIPT as the mutations are contributed from both parents thus it may present at various fractions in the mutation sites.…”
Section: Discussionmentioning
confidence: 96%
“…2A ). A previous study indicated that c.1153-3C > G resulted in a broken splice site and intron 6 retention and generated a premature termination codon ( 15 ). According to the ACMG/AMP Standards and Guidelines, this mutation was pathogenic (PS3 + PM2 + PM3_Strong + PP1 + PP4).…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxylation of these amino acids is crucial for the correct formation of collagen’s triple-helix structure. In the case of type VII, type VIII, and type IX OI, recessive mutations are found in three distinct components encoding the collagen prolyl 3-hydroxylation complexP3H1, CRTAP, and CyPB (encoded by PPIB). , These three proteins form a heterotrimeric complex in the ER, facilitating the folding of the triple helix and the PTM of the pre-collagen chain. The primary target of this complex is the modification of the Pro986 residue in collagen.…”
Section: Oi Pathogenesismentioning
confidence: 99%